LO42: Ice Cream Rounds: the adaptation and implementation of a peer-support wellness rounds in an emergency medicine residency training program. (15th May 2017) - Calder-Sprackman, S.M.; Kumar, T.; Sampsel, K.; Gerin-Lajoie, C.
Abstract : Introduction/Innovation Concept: Emergency Medicine (EM) is a specialty that requires physicians to deal with acutely ill patients in a fast-paced environment, which can create stress, mental exhaustion and burnout. Continually changing working teams in the Emergency Department does not always allow appropriate debriefing for difficult patient encounters and outcomes on shift. To address these challenges, we sought to adapt and implement a peer-support rounds called 'Ice Cream Rounds' used in some Pediatric training programs for an EM training program.Methods: CCFP and Royal College EM residents were surveyed to determine interest and need for Ice Cream Rounds. Of the 31/50 respondents, 87% (26/31) identified their co-residents as their main source of support after difficult patient encounters and 71% (22/31) felt that current opportunities to debrief after difficult experiences were only "sometimes" or "rarely" adequate. Overall, 84% (26/31) were interested in attending Ice Cream Rounds. Residents expressed that they did not want staff present for Ice Cream Rounds so two residents (SCS and TK) obtained training to lead peer-support sessions from The Faculty of Medicine Wellness Program. Attendance at rounds was voluntary and the EM program provided funding for refreshments. Two Ice Cream Rounds were piloted. Attendance and feedback was recorded from pilot sessions.Curriculum, Tool, or Material: Resident-only, peer-run confidential debriefing sessions. Sessions were voluntary and lasted one hour. Approximately 20-30/50 residents attended each Ice Cream Rounds. Discussions were confidential but include topics such as difficult patient encounters, poor patient outcomes, challenges in residency, and ethical issues. In response to positive attendance and feedback, the EM program provided 3-4 one-hour protected time slots with a stipend for refreshments for future academic years. Comments from residents consistently reaffirmed that Ice Cream Rounds was a helpful forum to discuss important issues with colleagues and provided a safe and confidential resource to help cope with residency challenges.Conclusion: We adapted, implemented, and evaluated a novel Peer-Support Wellness Rounds for debriefing resident issues and difficult patient encounters in a EM training program. To our knowledge this is the first Canadian initiative to implement such rounds in an EM training program. We believe that this template can be easily adopted by any EM training program and will effectively address wellness challenges faced by residents during their training.